Biodiversity of freshwater sponges (Porifera: Spongillina) from northeast Brazil: new species and notes on systematics - Nicacio, Gilberto; Pinheiro, Ulisses (Zootaxa, 2015)
Systematics and distribution of freshwater sponges is still poorly understood worldwide. This may be due to the scarcity of records, and the limited information about morphological traits used for taxonomy. Brazil has reportedly high species richness in the Neotropical Region; however, this diversity is likely to be significantly underestimated given that there are still many unexplored and poorly sampled areas, mainly in the north and northeast regions. We present here new locality records and taxonomic notes on three families and ten species of freshwater Porifera from northeast Brazil: Metaniidae (1), Potamolepidae (2) and Spongillidae (7). A new species of freshwater sponge is described here (Ephydatia caatingae sp.nov.). Additional notes on the systematics and biogeography of most of these species are also presented.